2021
DOI: 10.1177/00220345211028852
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of a Galanin-Coated Scaffold for Periodontal Regeneration

Abstract: The nervous system exerts finely tuned control over all aspects of the life of an organism, including pain, sensation, growth, and development. Recent developments in tissue regeneration research have increasingly turned to small molecule peptides to tailor and augment the biological response following tissue loss or injury. In the present study, we have introduced the small molecule peptide galanin (GAL) as a novel scaffold-coating agent for the healing and regeneration of craniofacial tissues. Using immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Using immunohistochemistry, GAL and GAL receptors were detected in the vicinity of healthy periodontal tissue and blood vessels, whereas the onset of periodontal disease resulted in the downregulation of GAL. Thus, GAL coating promoted periodontal regeneration and repaired periodontal defects generated in periodontitis model mice 63 . The low cost of mice and the availability of multiple transgenic strains allow for in‐depth mechanistic studies.…”
Section: Periodontal Models (Including Periodontal Defect Model and P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Using immunohistochemistry, GAL and GAL receptors were detected in the vicinity of healthy periodontal tissue and blood vessels, whereas the onset of periodontal disease resulted in the downregulation of GAL. Thus, GAL coating promoted periodontal regeneration and repaired periodontal defects generated in periodontitis model mice 63 . The low cost of mice and the availability of multiple transgenic strains allow for in‐depth mechanistic studies.…”
Section: Periodontal Models (Including Periodontal Defect Model and P...mentioning
confidence: 99%
“…This demonstrated that the PP‐pDA‐Ag‐COL scaffold exhibited enhanced pro‐osteogenic and antibacterial properties, and had much potential for treating alveolar/craniofacial bone regeneration 62 . In the study of Ma et al, 63 the small molecule galanin (GAL) was utilized as a novel scaffold coating agent for promoting the healing and regeneration of craniofacial tissues. Using immunohistochemistry, GAL and GAL receptors were detected in the vicinity of healthy periodontal tissue and blood vessels, whereas the onset of periodontal disease resulted in the downregulation of GAL.…”
Section: Periodontal Models (Including Periodontal Defect Model and P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Local injection of SP promoted bone formation during mandibular distraction osteogenesis in rats, and BDNF delivery from collagen sponges , or using hyaluronic acid hydrogels , led to increased bone, PDL, and cementum formation compared to scaffold controls. Galanin-loaded collagen sponges promoted bone formation in inflammatory periodontal defects . Overexpression of NTRN prior to irradiation was protective of salivary gland innervation and function, and laminin matrices with entrapped NTRN promoted neurite outgrowth from isolated parasympathetic submandibular ganglia (PSG), reduced neuronal apoptosis, and increased the number of end buds, progenitor cells, and innervation in mouse submandibular glands exposed to irradiation .…”
Section: Current Craniofacial Tissue Regenerative Approaches That Tar...mentioning
confidence: 99%
“…A novel pulp–dentin complex “tissue-chip” technology for high-fidelity studies of the tooth–material–microbiome interface is discussed (Rodrigues et al, 2021). Other articles inform on the regeneration of periodontal tissues (Ma et al, 2021) and bone using 3D-printed scaffolds (Chang, Lin et al, 2021). There also are several articles addressing modifications to implant surfaces for the purpose of enhancing bone–implant interactions and minimizing microbial infections at implant sites (Hasani-Sadrabadi et al, 2021; Ko et al, 2021; Rosa et al, 2021; Yang et al, 2021).…”
mentioning
confidence: 99%